Infrared Spectrum and UV-Triggered Transformations of Matrix-Isolated Meta-Fluorothiophenol Supported by Ground and Excited State Theoretical Calculations - Jesus, A. J. Lopes; Lucena Jr, J. R.; Rodrigues, G. P.; ILDIZ, GÜLCE ÖĞRÜÇ; do Monte, S. A.; FAUSTO, RUI (Wiley, 2025)
The infrared (IR) spectrum of meta-fluorothiophenol (mFTP) isolated in a low-temperature N-2 matrix was recorded and interpreted with the aid of B3LYP vibrational frequency calculations for both cis and trans conformers. Then, photochemical transformations in the matrix-isolated compound were triggered through UV-Vis laser irradiations and their outcomes were monitored by IR spectroscopy. Upon excitation at lambda = 285 nm, thiol-to-thione phototautomerization was identified as the sole reaction pathway, leading to the formation of three thione isomers. Among them, the ortho-isomer where the hydrogen atom reattaches to the fluorine-substituted side of the aromatic ring was identified as the predominant photoproduct. Identification of the photoproducts was confirmed by comparing the emerging experimental spectra with the IR absorptions predicted for the candidate structures. The photoreaction was found to be reversible, as irradiation at lambda = 405 nm partially restored the reactant. The experimental results were complemented with the application of multireference/multiconfigurational (CASSCF, CASPT2, MR-CIS) and TD-DFT (TD-M062X, omega B97XD, and tau-HCTHhyb) methods to investigate the excited state properties of mFTP, including the simulation of its UV photoabsorption spectra. A comparative analysis of the results obtained by the different methods was performed. This combined experimental and theoretical approach provided valuable insights into the photochemical behavior and electronic structure of fluorinated thiophenols.
Keywords: Matrix Isolation; Meta-fluorothiophenol; Multireference/multiconfigurational Methods; Photochemistry; Phototautomerization; Reversibility; Thiones